The director's cut : a novel - Thompson, Janice A. (Thompson, Janice A. Backstage pass, 2012)
Sitcom director Tia Morales is used to calling the shots and having everything securely in her control--that is, until a handsome cameraman turns both her heart and her life upside-down.